Mitigation of power quality problems using distribution static synchronous compensator: a comprehensive review - Barghi Latran, Mohammed; Teke, Ahmet; Yoldaş, Yeliz (IET power electronics, 2015)
Electric power quality (PQ) in distribution system has become increasingly significant subject both for end users and power suppliers with the deregulation of the electric power market. The inadequate performance of conventional compensation devices to mitigate PQ problems has revealed the use of advanced power electronics based compensation devices. Distribution static synchronous compensator (DSTATCOM) is one of the shunt connected custom power devices used to improve PQ, voltage and reactive power support and to increase the capability of the auxiliary service for utility grid. This study presents a comprehensive review of the various DSTATCOM configurations for single-phase (two-wire) and three-phase (three or four-wire) systems and control strategies for the compensation of different PQ problems in distribution systems. In addition, comprehensive explanation, comparison and discussion on DSTATCOM technology are performed. Furthermore, latest trends, practical consideration and some future research fields on DSTATCOMs are discussed in detail. This is intended to present a broad perspective on the status of DSTATCOM technology to researchers dealing with compensation of PQ problems in distribution systems.